(untitled) (Economics and region, 2023)
The purpose of the article is to study the role of chambers of commerce and industry in ensuring the foreign economic security of the state. As a result of the study of the works of a number of scientists, it was determined that "foreign economic security" is the economic state of the country, which produces competitive products and ensures a balanced trade balance. The components of foreign economic security were considered, and the most attention was paid to import and export security. As a result of the conducted research, measures to ensure export security of the state were considered, including economic, organizational and legal measures. Also, the state’s import security was analyzed, which represents the balance of imports in the ratio that is beneficial for the state’s economy. Next, tariff and non-tariff methods of import regulation were considered, including the consequences of the introduction of the import regime. Next, the Chamber of Commerce and Industry of Ukraine and its influence on the foreign economic security of the state, including through the Council on Foreign Economic Activities, were considered. The main prospects for further scientific research in this direction are the study of possible consequences of development and the search for new ways of influence of the Chamber of Commerce and Industry of Ukraine on foreign economic security.